TESTING OF CONCRETE PAVING BLOCKS THE BS EN 1338:2003 BRITISH AND EUROPEAN STANDARD CODE - Purwanto Purwanto; Yulita Arni Priastiwi (TEKNIK, 2008)
Concrete paving blocks are the choice for road and urban road’s surfacing. Besides their ease inapplication, they also provide design freedom by coloring off the material.Of major importance is their compression strength. The Indonesian SNI categorizes strength to theirpurposes i.e., for parking areas, pedestrian walking areas and heavy industrial estates.According to the SNI 03 – 0691 -1989 and British Standard BS 6717:1986 the strength of a paving blockis determined by the maximum carrying capacity under distributed load. The blocks are placed under acompression apparatus, and the compression strength at failure is recorded.As being observed in the field paving block’s failure pattern differs as to the failure under distributedloading. The paving’s failure mode is distinguished by a bending failure plain at the smallest crosssection.The BS EN 1338 code proposes a different approach. This paper will discuss the methods being used inthe BS EN 1338 code, and evaluates the effectiveness of Indonesian standards to date.